Контамінація як особливий спосіб словотворення у сучасній німецькій мові - Рись, Лариса Федорівна; Бєлих, Оксана Миколаївна; Rys, Larysa F.; Bielykh, Oksana M. (ROSTranse Trade F Z C company, 2017)
The article discusses blending as a little-investigated type of word formation in the modern German. In the paper blending is defined as a special type of word formation, as a process of intentional creation of a new word by joining parts of two or more words after clipping and/or where there is some form of phonemic overlap of the constituents. Blending is distinguished from other types of word formation such as composition and abbreviation. The basic word formation models of blends in the modern German are described; the structural characteristics of German blends are defined taking into consideration clipping and phonemic overlap in the process of combining lexemes to form a new word. Analysed type of word formation evidences that the described models of blends are productive word formation processes in the modern German language.
Keywords: blending; blend; clipping; overlap; word formation